The Communist Repression against the Families of “The Enemies of the People” in Romania. Case Study of Fr. Nyitrai Mózes - Budeanca, Cosmin (Komunizm: System - Ludzie - Dokumentacja, 2023)
In the first two decades after the Second World War over 100.000 political opponents or possible adversaries of communist regime in Romania were arrested, condemned, stripped off of their goods, and forced to spend several years in prisons. Those who survived and were eventually liberated, constantly wore the stigmata of their political condemnation, and the effects of these political condemnations had also a direct effect on their families. The family of the Unitarian priest Nyitrai Mózes was among the ones strongly affected by the communist repression. A part of its members were in prison, and for many years the family was separated. The underage children who remained at home had to deal with many complications. Those arrested faced several health problems. The entire family was affected by social and professional difficulties of integration, because of their “files” and the confiscation of their assets. The story of the Nitrayi family is just one out of many other stories of families who had to endure similar experiences during the Communist regime in Romania.